(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Credit risk is a standout amongst the most critical risks that banks confront, taking into account that giving credit is the fundamental capacity of business banks. In India, banks have assumed a vital job in economic growth and development. Since the 1970s, public sector banks (PSBs) have been in the cutting edge of assembling assets from far flung rural areas just as broadening banking services in the remotest parts of the nation. The financial performance of a bank is regularly estimated as the accomplishment of the bank regarding profitability position, benefit quality, consumer loyalty and other significant angles. The pressure of social plan has to a great extent been carried by PSBs with no pay. Accordingly, in the interest of keeping up credibility of PSBs which represent almost 70 percent of banking movement in the nation, the administration is supported in recapitalizing the PSBs consistently. The main aim of this paper is to characterize the impacts and cause relationship between the indicators of credit risk and profitability. Be that as it may, there is have to attempt look into on developing suitable standards, granular, for assessing performance of various banks working in India without smothering stream of credit to successful sectors.